Hubungan Sikap Ibu Hamil Trimester III Dengan Cakupan K6 Di Wilayah Kerja Puskesmas Gapura: The Relationship between the Attitudes of Pregnant Women in the Third Trimester and K6 Coverage in the Gapura Community Health Center Working Area - Pratiwi, Iva Gamar Dian; Mulyadi, Eko; Permatasari, Dian; Fatoni, Akhmad Feri (Chakra Brahmanda Lentera Institute, 2023)
Antenatal Care (ANC) is a health service that has been provided by health workers for mothers during their pregnancy. Visits of K6 pregnant women are pregnant women who receive standardized antenatal care at least six times, with the distribution of services once in the first trimester, once in the second trimester and twice in the third trimester and receive 90 Fe tablets during their pregnancy period in one region. work for a certain period of time. The World Health Organization (WHO) has set standards for carrying out ANC, at least 6 times during pregnancy. This research is an analytic observational research, namely research that explains the existence of a relationship between variables through hypothesis testing. In this study, sampling was taken using a cross-sectional sample size formula of 35 third trimester pregnant women who came for ANC. Data collection used a questionnaire as a data collection tool, data analysis used the Chi-squere test. It was found that most of the respondents had a positive attitude, namely as many as 21 people (60.0%). It is known that the coverage of K6 mothers in the work area of the Gapura Health Center is mostly fulfilled, namely 62.9%. The results of the statistical analysis showed that the p-value = 0.02 ≤ 0.05, meaning that it was concluded that there was a relationship between the attitude of third-trimester pregnant women and K6 coverage in the Working Area of the Gapura Health Center in 2022. There is a relationship between the attitude of third trimester pregnant women and K6 coverage in the Work Area of the Gapura Health Center in 2022, with a p-value = 0.02 ≤ 0.05.